ANALISIS TENTANG NILAI-NILAI KARAKTER DEMOKRATIS DALAM KEGIATAN BADAN EKSEKUTIF MAHASISWA (BEM) UNIVERSITAS RIAU - Bahri, Muhammad Syaiful; Erlinda, Sri; ', Hambali (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the values of the democratic character that are important to be cultivated to the whole society including students. Democracy is very important to the students, because students are the agent of change and the agent of control in a nation. The problem formulation of this research is Are There the Values of Democratic Character in the Activities of the Student Executive Board of Riau University? and Are There Obstacles in the Development of Democratic Process in the Student Executive Board of Riau University? This research is aimed to determine the values of the democratic character of the Student Executive Board of Riau University and to determine whether there are obstacles in the process of democratic development. The population of this research was 157 students of the Student Executive Board members of Riau University. In determining the sample, the researcher used proportional random sampling technique. The sample of this research was 40 respondents. The data were collected by observing, giving the questionnaire, interviewing, and doing literature technique. In analyzing the data, the researcher used quantitative descriptive analysis with percentage. Based on the result of this research, it can be concluded that the percent of the respondents who answered very often and often was 95.36%. If it is between 81.00% - 100%, it can be categorized that there are the values of democratic character, which are equal rights, equal participation, and the principle of majority. And also concludes that there is no obstacle in the development of democratic process in the Student Executive Board (BEM) of Riau University. It can be proven by the percent of the respondents who answered very often and often was 2.36%. If it is between 0.00% - 55.00% , it can be categorized that there is no obstacle in the development of democratic process.Keywords: Democratic Character, BEM